A Multi-Criteria Decision Analysis of Sustainability-Driven Marketing Strategies for Electric Vehicle Adoption in Emerging Markets - Banerjee, Prasoon; Gupta, Rahul; Singh, Ajay; Saxena, Ashima; Banerjee, Sonali (Indian Journal of Marketing, 2026)
Purpose : The purpose of the study was to analyze the effectiveness of marketing strategies for sustainable products, electric vehicles (EVs) in particular, and the role played by consumers to evaluate it. Since there has been increased public interest in sustainable motoring, there has been an acknowledgment that the success of EV marketing lies not just in the policies but in how they can be perceived by those who are influenced by various sustainability issues. The paper identified what matters in terms of sustainability as far as the adoption of EVs consumers are concerned. Methodology : A step-wise-step mixed-methods approach was used in the study. The thematic analysis was used in the first phase, which is qualitative analysis. The qualitative data were collected through an online open-ended survey with 200 potential EV consumers from India’s National Capital Region. This was conducted to identify the factors of sustainability that showed influence on the purchase decision of the customers. These factors were incorporated into an Analytic Hierarchy Process (AHP) framework. This was the second phase of the study. The survey participants were asked for pairwise comparisons of the criteria, and the resulting data were obtained from 120 participants, but only 98 complete comparisons were used for analysis. The AHP results were computed using R sosftware. Findings : Through the findings, it was notable that brand trust and credible certification had the most significant role in the assessment of sustainability-focused EV marketing by consumers. There were two factors that ranked high but to a lesser extent, those factors were communication reach and environmental concern. Affordability and incentives were also assessed, and these are considered to be relatively less influential for the group of consumers included in this study. By the comparison made of the specific strategies, it was observed that green certifications ranked top, followed by social media campaigns and corporate social responsibility initiatives. Influencer marketing was accorded the lowest priority primarily due to issues of credibility and authenticity. Practical Implications : The results highlighted that sustainability, keeping in consideration practical implications, was important. Eco-certifications, environmental claims, and third-party verification seemed to play an important role in consumers trusting the technology. Communication channels should target to reduce or remove these environmental claims and concentrate on long-term values. The main attention area of EV marketing should be clearing doubts and increasing trust levels related to EV technologies. Originality : The study has highlighted the bringing together of consumer insights and structured decision-making within a single framework. The study integrated the qualitative consumer perspectives with the AHP, unlike the prior studies, which only examined the EV adoption factors. The result was a practical, consumer-informed approach for evaluating and prioritizing sustainability-driven EV marketing strategies, particularly suited for emerging market contexts.